Impactos dos gastos do governo sobre o IDHM: um estudo para os municípios baianos - Conceição Filho, Antônio Mascarenhas da (2024)
The investments that the Government makes play a central role in the economic development of localities, as a nation, a State, a municipality or any territory, influencing economic growth, quality of life and the well-being of residents. Effective public policies and strategic investments can help promote sustainable, inclusive and equitable local development, creating an environment conducive to the economic and social progress of communities. In this context, this dissertation analyzes the impacts generated by public investments, divided by functions, on the development of municipalities, represented by the IDHM. In this way, a Panel Data model is estimated for the years 2000 to 2010, covering 416 municipalities in Bahia. Taken together, the results point to positive and statistically significant impacts on spending on health, education and housing, contributing to the improvement in the development of the municipalities analyzed.